Nephrotoxicity of piroxicam in rats - (:unkn) unknown (My University, 2003)
The aim of this study was to investigate the nephrotoxicity of piroxicam in rats. Spraque-Dawley albino rats were treated with 1.4 mg/kg/day or 2.8 mg/kg/day piroxicam i.p. for 10 days. No significant changes were observed in the following parameters: serum cystatin-C, serum uric acid, serum potassium, urine volume, and potassium output. A small but significant (p<0.05) decrease in serum total protein and albumin were observed. A significant increase in microalbuminuria occurred after 10 days of treatment with 2.8 mg/kg piroxicam. No histopathological changes were observed in kidneys of rats treated with 2.8 mg/kg/day piroxicam. The results indicate that piroxicam has no significant effect on renal function in rats, a finding which corresponds with case reports in the literature. In the literature, most of the piroxicam induced cases of nephrotoxicity were seen in older patients. We conclude that piroxicam can be used safely in healthy subjects for short time periods. Its use should, however, be monitored and limited in the elderly and in congestive heart failure, chronic kidney failure, liver cirrhosis and where concomitant use of diuretics is indicated.
Keywords: Biochemical parameters; Cystatin-C; Nephrotoxicity; Piroxicam